Absorption of Polyunsaturated Fatty Acid (PUFA) Is Related to IgG Blood Levels of Neonatal Pigs during the First 48 Hours Postpartum - Kateryna Pierzynowska; Jarosław Woliński; Björn Weström; Radosław Jazwiec; Halyna Shmigel; Stefan G. Pierzynowski (Journal of Immunology Research)
The current study is aimed at highlighting the impact of enterally or parenterally applied immunoglobulins (Igs) on polyunsaturated fatty acid (PUFA) absorption in newborn pigs. Piglets were chosen as the appropriate model since they are born agammaglobulinemic and any effects of Ig addition can thus be easily monitored. Twenty-one, new born piglets were used in the study. Plasma levels of PUFAs, ARA, DHA, and EPA dropped (similarly to that seen in human infants) by between 40 and 50% in newborn, unsuckled piglets fed an infant formula for 48 h. However, piglets fed the same infant formula but supplied with immunoglobulins (Igs) either orally, by feeding piglets with swine or bovine colostrum, or intravenously, by i.u.a. (intraumbilical artery) infusion of swine or human Ig preparations or swine serum, demonstrated improved growth and PUFA levels similar to those observed at birth. The significant positive correlation was found between the body weight gain, as well as levels of ARA and EPA, and plasma immunoglobulins concentration. These results indicate the importance of the presence of Ig in the blood for appropriate absorption of dietary PUFAs and probably other nutrients in newborn piglets. This may have an impact on the dietary guidelines for human neonates, especially those born prematurely with low plasma Ig levels, since PUFAs are important factors for brain development in early life.